PENGEMBANGAN PAKET PERKULIAHAN READING BERKELANJUTAN JURUSAN PENDIDIKAN BAHASA INGGRIS UNDIKSHA - Artini, Luh Putu (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2017)
This research aims at developing the syllabus and instructional materials for Reading course series in English Education Department, Ganesha University of Education. This Reading course comprises four series: Reading I (Literal Reading), Reading II (Intepretive Reading), Reading III (Critical Reading) and, Advanced Reading (Reading from the Media). The research was inspired by preliminary findings about unclear transition and focus of each serial of reading course. These include the degree of complexity and coverage of the texts, instructional strategies and teaching strategies. As a matter of fact, reading is a stepping stone for developing other language skills such as writing, speaking and listening (Guthrie& Kirsch, 2007). The first year of the research has resulted in the adapted syllabus and blueprint for the material development. In the second year the instructional materials for levelled reading courses were developed and validated and was checked its relevance and readability. Data analysis found that the product was highly relevant to the syllabus and provide with Engliah language teaching. This indicates that the quality of the product can be categorized as very good and as systematic gradation, focus, depth and scope.